Sharing of Misinformation during COVID-19 Pandemic: Applying the Theory of Planned Behavior with the Integration of Perceived Severity. Issue 2 (3rd April 2022) - Alwreikat, Asma
ABSTRACT: This study investigates the behavioral intention to verify information before sharing during COVID-19 pandemic. The sample consisted of 210 Library and Information Science (LIS) students from three LIS departments. The Theory of Planned Behavior (TPB) constructs and the perceived severity construct were used to check respondents' behavior. The results of the data analysis revealed that respondents showed high levels of perceived behavioral control and attitude toward intention to verify information before sharing. However, Subjective norms and perceived severity appeared to have insignificant effect on respondents' information sharing behavior. The findings of the study highlights the importance of information literacy skills to overcome chaos of misinformation spreading on social media platforms.